Perancangan konsep sistem monitoring untuk proyek pengembangan perangkat lunak pada dinas pemerintah kota manado - Christopel Hamonangan Simanjuntak; I Gede Atmaja; Stieven Natanel Rumokoy; Anang Setiaji; Fata Nidaul Khasanah (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
Government activities that can be assisted by applications or software such as registration, making family cards or registration for making identification cards and others. The demand for making applications has become so many from existing agencies that it causes new problems. For example, there is no monitoring of software development which makes it difficult for employees in related agencies to know when the system can be used and cannot know the progress of making their applications. Another problem is that the absence of a computerized monitoring scheme results in systems or applications ordered by existing agencies becoming irregular. In the old order flow, communication about the development of the system with the development team always cannot be directly communicated because the ordering office cannot give direct notes based on problems in the system so that the trouble accumulates. Based on existing problems, the concept of a monitoring system for software development or software was developed which can accommodate these problems. This concept is developed in several stages, namely literature study and data collection, needs analysis, concept design design, analysis and evaluation of existing concepts. The result of the existing design is a context diagram containing 3 actors and 1 system that is related to each other. In addition, there is a sequence diagram for the request system where there are 2 actors, namely the Agency and the Development Team who are interconnected in completing the contract for making the system / application ordered. It is hoped that the concept of this monitoring system can help the government in monitoring and regulating software development, especially within related agencies in the Manado city government.